Moderasi Beragama Habib Utsman Bin Yahya dalam kitab Adabul Insan dan implikasinya pada pembelajaran PAI - Siti Maria Ulfah; Andy Hadiyanto; Abdul Fadhil (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2024)
This study aims to analyze and describe Habib Uthman bin Yahya's thoughts regarding religious moderation in aspects of non-violence (al-la 'Unf), culturally friendly (I'tiraf al 'urf), fair and upright (I'tidal), respecting the nation state. (Al-Muwathanah), exemplary (Qudwah) especially in the book Adabul Insan and its implications for learning Islamic Religious Education. This research is included in the type of qualitative research with a library research approach. Data collection techniques were carried out through literature studies and interviews. The data analysis in this study used the theory of religious moderation. The results showed that in the aspect of anti-violence (al-la 'Unf) religious moderation was shown by being gentle, not disturbing one another, helping each other without discrimination, empathizing, respecting each other and spreading love among human beings. Aspect (I'tiraf al 'urf) it is shown by understanding and acceptance of the existence of community culture, looking for a middle way between local customs and Islamic law, and respecting and appreciating the culture carried out by the local community. The I'tidal aspect is shown in the attitude of maintaining a balance between rights and obligations, acting fairly both in speech and deed, having a stand and being proportional in judging something. The Al-Muwathanah aspect is manifested in a responsible attitude as a citizen and not rebelling against a legitimate and just government. Whereas in the Qudwah aspect, it is shown by a creative, innovative, diligent, initiative, and maintaining trust. Habib Uthman bin Yahya's thought of religious moderation can be implied in PAI.